Kniga poteri͡annykh veshcheĭ - Connolly, John, 1968- (Ėksmo ; Domino, 2011)
Taking refuge in fairy tales after the loss of his mother, twelve-year-old David finds himself violently propelled into an imaginary land in which the boundaries of fantasy and reality are disturbingly melded.